Paying zakat to muslim and giving hibah to non-muslim / Norshahira Azman … [et al.] - Azman, Norshahira; Patul Muin, Fairuz Irdina; Mohamed, Nur Shahida; Azhan, Siti Khairul Aisyah; Mohd Ali, Nursyahida (2023)
Islam is a beautiful religion. In Islam, zakat is the fourth pillar of Islam, a pillar that must be fulfilled by every Muslim who meets the requirements. Zakat is to issue a certain amount of property to be given to the eight groups of asnaf who are entitled to receive it. The payment of zakat is said to clear the annual income. By issuing zakat, it can bridge the gap between the rich and the poor. The amount of zakat is also based on income and property value. The minimum amount to be paid is as much as 2.5% of a Muslim's total savings and wealth.